The issue of social inclusion of the Roma minority in the Czech republic from the viewpoint of the Model of the culturally – minded and adapted care - Toumová, Kristýna; Tóthová, Valérie; Olišarová, Věra (Magyar Egészségügyi Szakdolgozói Kamara, 2019)
Objective: The aim of the research was to map out the area of social inclusion of the Roma minority according to the Model of culturally-minded and adapted care. Above all to find out the subjective opinion of the Roma on their lives in the Czech Republic, the distribution of family roles or the respect of Roma traditions and customs.Methods: Data collection was carried out using a quantitative survey, in the form of a non-standardised questionnaire. The research group consisted of 600 members of the Roma minority across the Czech Republic. Results: The results show that the Roma minority feels some intolerance, in some cases even discrimination from the majority of society. Although in a Roma family the traditional division of the roles of the mother - maternal role, the father - the family breadwinner persists, these roles change slightly depending on the style of family upbringing and cohabitation with the older generations. The life of a Roma according to Roma traditions and customs subsides slightly into the background. Younger and single Roma no longer follow traditions like their parents. Therefore, there is an obvious large influence from the majority of society towards the Roma minority. Conclusion: The Roma minority is a group of people with many specifics. To coexist with a majority society, therefore, there is a need for understanding and tolerance on both sides. For a better understanding of this minority, the conceptual model of the following authors J. N. Giger and R.E. Davidhizar can help us, as it complexly approaches the specific needs of an individual with a different culture or religion.
Problematika sociálního začlenění romské minority v České republice z pohledu Modelu kulturně ohleduplné a uzpůsobené péče
Keywords: Roma; Socialisation; culturally unique individual; Romové; socializace; J. N. Giger a R. E. Davidhizar; kulturně svébytný jedinec